Evaluación del control de inundaciones utilizando la técnica por la infraestructura verde SUDS en la Alborada - Guzhñay Márquez, Lady Yomayra (2024)
This research work focuses on Green Infrastructure through the use of sustainable urban drainage systems for flood control, which has the capacity to establish the storage, infiltration, evaporation or retention of runoff at a given point of origin. in order to avoid the collapse of the storm sewer system. Therefore, the objective was to evaluate the green infrastructure (SUDS) for flood control under the characteristics of the rain gardens in the La Alborada sector, Av. Benjamín Carrión. The methodology used was a non-experimental design, because prior manipulation of the variables under study is not required, with a mixed approach based on the collection and analysis of numerical and characteristic information on the risks caused by floods, the same as focused on a descriptive and exploratory scope. The survey and interview carried out with 384 inhabitants of Av. Benjamín Rosales were used. Where evidence was achieved of the need to establish a green infrastructure model with the application of sustainable urban drainage systems on Av. Benjamín Carrión for flood control through a filtering system, where the use of rain gardens was proposed as an alternative. that maintain a dimension of 3.6m2 each, with the use of the red acacia tree plant, in order to implement this type of structures within specific areas so that they evacuate a greater volume of runoff, contributing to flood control in the urban roads of the city of Guayaquil.